Analisis Pendekatan Contextual Teaching and Learning (CTL) untuk Mendukung Pencapaian SDGs dalam Pembelajaran Biologi - Dian Pratiwi; Moh Usamah; Nurulita Luthfia Salsabilla; A’idah Muflichatul Maghfiroh; Madinatul Munawarah; Murni Sapta Sari (Jurnal Cakrawala Pendidikan dan Biologi, 2024)
The Contextual Teaching and Learning (CTL) approach effectively enhances meaningful and relevant biology learning while fostering critical thinking, creativity, and problem-solving skills. By aligning with sustainable education principles, CTL supports the achievement of SDGs and equips students to address global challenges. It is recommended that educators receive training to design CTL-based strategies, integrate local and global themes, and explore its application across diverse educational contexts and models.